Law Enforcement of the Crime of Embezzlement of Land Certificates, Case Study of the Bali High Prosecutor's Office - Dewi, Ni Kadek Fany Puspita; Wiratny, Ni Ketut; Damanik, Siti Nurmawan (Ridwan Institute, 2025)
This research is entitled